2023
DOI: 10.3389/fcell.2023.1296986
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting mechanistic susceptibilities of hematopoietic and endothelial stem-progenitor cells in respective pathogeneses of HIV-1 and SARS-CoV-2 infections

Prasad S. Koka,
Bharathi Ramdass

Abstract: The multitude of cellular types can be expected to behave differently when receiving invading pathogens such as mammalian viruses. The nature-dictated causes for such intrinsic cellular diversity become the criteria for the emergence of specific virus-receptor interactions on that particular host cellular surface, in order to accommodate contact with various other living entities whether desirable to the host or not. At present, we are presented with an example of two contrasting behaviours wherein the well-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Thus, our observations were the first reported findings linking HIV-1 infection to dynamic differential regulation of specific miRNAs, which in turn inhibit hematopoiesis to cause virus-induced hematological disorders in infected patients with HIV/AIDS ( Padmanabhan et al, 2020 ). Homeobox gene-encoded transcriptomes are expected to play an important role in the onset of cytopenias ( Koka and Ramdass, 2023 ). Furthermore, herein we show that ( Figure 2 ) HIV-1 infection caused changes in microRNA that disrupt homeobox HOXB3 versus control GAPDH messenger RNA ( Zhou et al, 2001 ) , with the consequences of inhibiting hematopoiesis due to the loss of HOXB3 messenger RNA expression ( Figure 2 ) ( Sauvageau et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our observations were the first reported findings linking HIV-1 infection to dynamic differential regulation of specific miRNAs, which in turn inhibit hematopoiesis to cause virus-induced hematological disorders in infected patients with HIV/AIDS ( Padmanabhan et al, 2020 ). Homeobox gene-encoded transcriptomes are expected to play an important role in the onset of cytopenias ( Koka and Ramdass, 2023 ). Furthermore, herein we show that ( Figure 2 ) HIV-1 infection caused changes in microRNA that disrupt homeobox HOXB3 versus control GAPDH messenger RNA ( Zhou et al, 2001 ) , with the consequences of inhibiting hematopoiesis due to the loss of HOXB3 messenger RNA expression ( Figure 2 ) ( Sauvageau et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…These CD34 + HSPCs’ fate changes result in altered terminally differentiated lineages of the multipotent HSPCs. Based on our published results ( Padmanabhan et al, 2020 ), we hypothesize that upon HIV-1 infection of the CD4 + thymocytes, the observed differential regulation of miR-15a and miR-24 that occurs causes abnormal post-transcriptional regulation of specific HOX gene-encoded transcriptomes ( Koka and Ramdass, 2023 ). Loss or abnormal translational entities, in turn, affect specific MAPK signaling and CD34 + cell fate, causing the dysregulation of hematopoiesis.…”
Section: Changes In Specific Hox Mrna Expression Levels Due To Post-t...mentioning
confidence: 99%